Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1440-1843.2011.01977.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of microorganisms in exhaled breath condensate during acute exacerbations of COPD

Abstract: Bacterial nucleic acids can be identified in EBC of COPD patients with exacerbations. The results obtained from EBC and sputum did not correlate well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…In the context of ECOPD, detection rates of some of the sampled biomarkers, notably cytokines, have been particularly low [23,24] whereas for inflammatory mediators of a peptide nature, better detection rates have been achieved with albumin-coated sampling devices [23]. Studies comparing EBC, sputum or BAL in the context of ECOPD are scarce [24-26]. …”
Section: Resultsmentioning
confidence: 99%
“…In the context of ECOPD, detection rates of some of the sampled biomarkers, notably cytokines, have been particularly low [23,24] whereas for inflammatory mediators of a peptide nature, better detection rates have been achieved with albumin-coated sampling devices [23]. Studies comparing EBC, sputum or BAL in the context of ECOPD are scarce [24-26]. …”
Section: Resultsmentioning
confidence: 99%
“…A study comparing EBC and sputum samples from asthma patients showed a 100% overlap in the culturable fungi identified between the two sample types (5), and a study examining the bacterial pathogens cultured from BAL and EBC samples in patients with ventilator-associated pneumonia showed a high concordance between the two sampling methods (16). In comparison, when PCR assays for 10 common respiratory pathogens were performed on EBC and sputum samples from chronic obstructive pulmonary disease patients, the results were found not to correlate well (17). EBC collection has also previously been found to be inefficient for detecting Mycobacterium tuberculosis (18), influenza viruses (19), and the common cystic fibrosis pathogens Pseudomonas aeruginosa and Burkholderia cepacia (20).…”
Section: Discussionmentioning
confidence: 99%
“…Microbiological studies in COPD have been limited to the detection of specific respiratory pathogens such as P. aeruginosa , M. catarrhalis, and H. influenza [6], [7] by means of cultural methods or pathogen-specific PCR. The application of culture independent methods to detect the presence of microorganisms has been introduced to characterize the microbiome of various organs [8].…”
Section: Introductionmentioning
confidence: 99%